OPTIMALISASI METODE TASYJIR DALAM PEMBELAJARAN KITAB SAFINATUS SHOLAT DAN RELEVENSINYA TERHADAP PEMBELAJARAN FIQIH MADRASAH IBTIDAIYYAH - Saifulloh Saifulloh; Itsnaini Alwi (STKIP Subang, 2026)
The application of systematic instructional methods in the teaching of classical Islamic texts plays an important role in achieving learning objectives, enhancing students’ understanding, and strengthening their memory of fiqh materials, particularly in the study of Safinatus Sholat. This study aims to analyze the optimization of the Tasyjir method or Mind Mapping (according to Tony Buzan) in the learning of Safinatus Sholat and its relevance to Fiqh learning at the Madrasah Ibtidaiyyah level. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation. The findings indicate that: (1) the implementation of the Tasyjir method in learning Safinatus Sholat at Pondok Pesantren Darussunnah, Sragen, in the 2025–2026 academic year had a positive impact on students’ understanding of fiqh, as reflected in active interaction between students and teachers; (2) the Tasyjir method contributed to improving students’ conceptual understanding of fiqh learning in a more systematic manner; and (3) the method strengthened students’ memory of the content of the studied text through structured visual representation. However, several inhibiting factors were identified, including limited instructional time and differences in students’ abilities to quickly process and comprehend visual information.